Environmental and Qualitative Monitoring of a Transoceanic Intermodal Transport of Melons - Eva Cristina Correa; Noelia Castillejo; Pilar Barreiro; Belén Diezma; Miguel Garrido-Izard; Jossivan Barbosa Menezes; Encarna Aguayo (Agronomy, 2022)
To supply the off-season melon market, Europe imports from distant markets in other countries, mainly Brazil. Cold transportation takes at least 15–20 days, thus increasing the risk of quality losses. Moreover, product deliveries, especially in international markets, can result in supply chain inefficiencies that negatively affect carbon footprint and expected freshness. Implementing quality sensors and advanced cold chain management could help to reduce these problems. The objective of this work was to monitor a real transoceanic intermodal transport of melons (Brazil to Spain), through the implementation of multi-distributed environmental sensors (15 ibuttons loggers) to evaluate the remaining shelf-life (RSHL) of melons at destination. The sensors’ location within the cargo reached a maximum variability range of 4 °C. Using digital sensors to track temperature variations, it was verified that in different locations in the container, the melon RSHL at the end of the journey, was nine days and 19 h in colder spots, while in the hottest spot, the RSHL was reduced to five days and 22 h. This fact has substantial implications for improved tracking of temperature to maintain fruit quality for market, potentially reducing waste, and contributing to higher profit margins for international food supply chains.